Nivel de calidad de vida y factores asociados en pacientes hipertensos del primer nivel de atención, Loreto 2023 - Moreno Correa, Boris Jefferson (2023)
Arterial hypertension is a public health problem worldwide, it is important to identify the level of quality of life and associated factors in these patients to improve mortality and sequelae in them. The objective of the research was to determine the level of quality of life and the associated factors in hypertensive patients who are treated at the first level of care in the Loreto region in 2023. A type of analytical, cross-sectional, and observational study was carried out. The level of quality of life was associated with socioeconomic history, pathological history, and quality of care by health personnel. 225 surveys were analyzed, where 45% of the hypertensives had an inferior quality of life and the remaining 55% had an excellent quality of life. Socioeconomic background was found as factors associated with quality of life: Gender: female (X2=8.835; p=0.003), marital status: single, divorced, and widowed (X2=12.887; p= 0.012) and monthly salary: less than 1025 soles (X2=6.111; p=0.013), medical history: comorbidities: lung pathology (X2=4.102; p=0.043) and renal pathology (X2=7.102; p=0.008) and control disease: uncontrolled patients (X2=10.617; p=0.001); however, no association was found between quality of life and quality of care by health personnel. Hypertensive patients who are seen at the first level of care have an excellent quality of life. Socioeconomic background (gender, marital status, and monthly salary) and pathological history (comorbidities and disease control) are associated with the level of quality of life of hypertensive patients.